2010
DOI: 10.4103/0976-237x.72779
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of clinical/radiographical signs of mineral trioxide aggregate and formocresol on pulpotomized primary molars

Abstract: The objectives of this study were (1) to evaluate clinically and radiographically the effects of mineral trioxide aggregate (MTA) as a pulp dressing after coronal pulp amputation (pulpotomy) in primary molars, (2) to compare the effects of MTA and formocresol in pulpotomized primary teeth. Sixty primary mandibular molars of thirty healthy children aged between 5-8 years were treated by conventional pulpotomy technique. The teeth on the right side are assigned to MTA (Group A) and the left side for the Formocre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 7 publications
3
15
0
6
Order By: Relevance
“…MTA appears to be superior to formocresol and could serve as a suitable replacement, but generally costs more than formocresol. [17][18][19] Although the use of formocresol has been questioned, a recent study showed that the clinical and radiographic success rates for the formocresol at 12 months were 97% and 87%, respectively. These rates were higher than alternatives methods for pulpotomy (diode laser and ferric sulfate).…”
Section: Discussionmentioning
confidence: 99%
“…MTA appears to be superior to formocresol and could serve as a suitable replacement, but generally costs more than formocresol. [17][18][19] Although the use of formocresol has been questioned, a recent study showed that the clinical and radiographic success rates for the formocresol at 12 months were 97% and 87%, respectively. These rates were higher than alternatives methods for pulpotomy (diode laser and ferric sulfate).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure preserves the vitality of the remaining pulp and helps retain the tooth in a desirable state until normal exfoliation occurs. For these purpose, mineral trioxide aggregate (MTA) has been successfully used as an alternative to formocresol [2][3][4][5][6][7][8][9][10][11] and calcium hydroxide 12,13) due to its favorable physical and biological properties. It is composed mainly of Portland cement, with bismuth oxide included as a radiopacifier.…”
Section: Introductionmentioning
confidence: 99%
“…A manutenção da dentição decídua, sem perdas prematuras, preserva a integridade dos arcos e as funções do sistema estomatognático, previne hábitos deletérios e assegura o desenvolvimento do crescimento facial normal (CAICEDO et al, 2006;FUKS, 2008;SUBRAMANIAM et al, 2009;BLANCHARD;HUGAR;DESHPANDE, 2010;COLL, 2010;GODHI;SOOD;SHARMA, 2011;HUTH et al, 2012).…”
Section: Ingaalpunclassified
“…Como no presente estudo, este tipo de monitoramento a partir de exames clínicos e radiográficos longitudinais é consolidado e aceito na literatura (AGAMY et al, 2004;NEAMATOLLAHI;TAJIK, 2006;CASTRO;PINTO, 2006;AEINEHCHI et al, 2007;MORETTI et al, 2008;ALAÇAM et al, 2009;FORNETTI et al, 2009;SAKAI et al, 2009;HUGAR;DESHPANDE, 2010;ERDEM et al, 2011;MALEKAFZALI;SHEKARCHI;ASGARY, 2011;JAYANTHI, 2011;ODABAS et al, 2011;HUTH et al, 2012;RUBY et al, 2013;FERNÁNDEZ et al, in press).…”
Section: Metodologiaunclassified
See 1 more Smart Citation